Subtotal nephrectomy accelerates pathological cardiac remodeling post-myocardial infarction: Implications for cardiorenal syndrome - Liu S. (2014)
Background To further understand the pathophysiology of concomitant cardiac and renal dysfunction, we investigated molecular, structural and functional changes in heart and kidney that occur when a kidney insult (5/6 nephrectomy-STNx) follows myocardial infarction (MI). Methods Male Sprague Dawley rats (n = 43) were randomized into four groups: Sham-operated MI + Sham-operated STNx (Sham + Sham), MI + Sham-operated STNx (MI + Sham), Sham-operated MI + STNx (Sham + STNx) and MI + STNx. MI/Sham surgery was followed by STNx/Sham surgery 4 weeks later. Cardiac and renal function was assessed prior to STNx/Sham surgery and again 10 weeks later. Hemodynamic parameters were measured prior to sacrifice. Results Compared to the MI + Sham group, STNx further accelerated the reduction in left ventricular (LV) ejection fraction by 21% (p < 0.01), and increased tau logistic by 38% (p < 0.01) in MI + STNx animals. Heart weight/body weight (BW) and lung weight/BW ratios were 39% (p < 0.001) and 16% (p < 0.01) greater in MI + STNx compared to MI + Sham animals. Similarly, myocyte cross-sectional area (p < 0.001), cardiac interstitial fibrosis (p < 0.01) and collagen I (p < 0.01) were increased in the LV non-infarct zone of the myocardium in the MI + STNx group. These changes were associated with significant increases in atrial natriuretic peptide (p < 0.001), transforming growth factor β1 (p < 0.05) and collagen I (p < 0.05) gene expression in MI + STNx animals. In comparison with the Sham + STNx group, renal tubulointerstitial fibrosis was increased by 64% in MI + STNx animals (p < 0.001), with no further deterioration in renal function. Conclusions STNx accelerated cardiac changes post-MI whilst MI accelerated STNx-induced renal fibrosis, supporting bidirectional interactions in cardiorenal syndrome (CRS). This animal model may be of use in assessing the impact of therapies to treat CRS. © 2013 Elsevier Ireland Ltd. All rights reserved.